Glocalization Tendency in Local Newspapers "Merhaba Arapça" Case - (:unkn) unknown (My University, 2015)
0

As Marshall McLuhan already mentioned, technological developments in communication turned the world to "a global village". Boundaries on time and space shattered and new information technologies changed the views on "globality". A new understanding emerged by defining globalization a process that local properties become prominent. In a global news environment that the news material is standardized, local news gathering becomes a vital source. While global media organizations make local elements a part, adaptation capabilities of local elements to global news system is notable. In this study glocalization tendency will be discussed on a local newspapers' activities to engage with the process of going from local to global as an example. "Merhaba Arapça" is a Konya based newspaper having a strategy "to go from local to global" reflecting a new trend in local media and will be our focus of study. In this study we will briefly discuss globalization with respect to glocalization theory and reflections of it in the newspaper field. And finally investigate the consequences on "Merhaba Arapça" example